The Influence of Social Media Influencers, E-wom and Perceived Quality on Purchase Intention on E-commerce Platforms (A Study of TikTok Shop Among Gen Z Jabodetabek - Cladio, Giofano; Wardani, Deni (Indonesia Banking School, 2024)
This study aims to examine “The Effect of Social Media Influencers, E-Wom, and Perceived Quality on Purchase Intention on the E-Commerce Platform (An Examination of TikTok Shop among Gen Z in Jabodetabek)”. The independent variables in this study are Social Media Influencers, E-Wom, and Perceived Quality. While the dependent variable in this study is Purchase Intention. Hypothesis testing in this study uses the PLS or partial Least Square method with SmartPLS 3.0 software. The data collection technique uses a Google Form application questionnaire to collect respondent information. The sample in the study was prospective buyers at TikTok Shop among Gen-Z in Jabodetabek, totaling 92 respondents. The results of the analysis show that Social Media influencers have a significant and positive effect on Purchase Intention. E-Wom has a significant and positive effect on Purchase Intention and Perceived Quality has a significant and positive effect on Purchase Intention.